Research can be integrated into public health policy-making: global lessons for and from Spanish economic evaluations - Marta Trapero-Bertran; Subhash Pokhrel; Stephen Hanney (BMC, 2022)
Abstract WHO promotes the use of research in policy-making to drive improvements in health, including in achieving Sustainable Development Goals such as tobacco control. The European Union's new €95 billion Horizon Europe research framework programme parallels these aims, and also includes commitments to fund economic evaluations. However, researchers often express frustration at the perceived lack of attention to scientific evidence during policy-making. For example, some researchers claim that evidence regarding the return on investment from optimal implementation of evidence-based policies is frequently overlooked. An increasingly large body of literature acknowledges inevitable barriers to research use, but also analyses facilitators encouraging such use. This opinion piece describes how some research is integrated into policy-making. It highlights two recent reviews. One examines impact assessments of 36 multi-project research programmes and identifies three characteristics of projects more likely to influence policy-making. These include a focus on healthcare system needs, engagement of stakeholders, and research conducted for organizations supported by structures to receive and use evidence. The second review suggests that such characteristics are likely to occur as part of a comprehensive national health research system strategy, especially one integrated into the healthcare system. We also describe two policy-informing economic evaluations conducted in Spain. These examined the most cost-effective package of evidence-based tobacco control interventions and the cost-effectiveness of different strategies to increase screening coverage for cervical cancer. Both projects focused on issues of healthcare concern and involved considerable stakeholder engagement. The Spanish examples reinforce some lessons from the global literature and, therefore, could help demonstrate to authorities in Spain the value of developing comprehensive health research systems, possibly following the interfaces and receptor model. The aim of this would be to integrate needs assessment and stakeholder engagement with structures spanning the research and health systems. In such structures, economic evaluation evidence could be collated, analysed by experts in relation to healthcare needs, and fed into both policy-making as appropriate, and future research calls. The increasingly large local and global evidence base on research utilization could inform detailed implementation of this approach once accepted as politically desirable. Given the COVID-19 pandemic, increasing the cost-effectiveness of healthcare systems and return on investment of public health interventions becomes even more important.